Sericin/Human Placenta-Derived Extracellular Matrix Scaffolds for Cutaneous Wound Treatment-Preparation, Characterization, In Vitro and In Vivo Analyses - Jayavardhini Bhoopathy; Sankari Dharmalingam; Weslen Vedakumari Sathyaraj; Selvarajan Rajendran; Shibormi Rymbai; Rethinam Senthil; Raji Atchudan (MDPI AG, 2023)
Human placenta is loaded with an enormous amount of endogenous growth factors, thereby making it a superior biomaterial for tissue regeneration. Sericin is a naturally occurring silk protein that is extensively used for biomedical applications. In the present work, sericin and human placenta-derived extracellular matrix were blended and fabricated in the form of scaffolds using the freeze-drying method for cutaneous wound treatment. The prepared sericin/placenta-derived extracellular matrix (SPEM) scaffolds were characterized to determine their morphology, functional groups, mechanical strength, and antibacterial activity. Scanning electron microscopic analysis of the scaffolds showed smooth surfaces with interconnected pores. In vitro MTT and scratch wound assays performed using HaCaT cells proved the non-toxic and wound-healing efficacy of SPEM scaffolds. In vivo CAM assay using fertilized chick embryos proved the angiogenic potency of the scaffolds. Animal experiments using Wistar albino rats proved that the open excision wounds treated with SPEM scaffolds significantly reduced wound size with collagen deposition. These results confirm that SPEM scaffolds can serve as a promising biomaterial for tissue regeneration.